Does high-intensity running to fatigue influence lower limb injury risk? - Rice, H.; Starbuck, C.; Willer, J.; Allen, S.; Bramahm, C.; Jones, R.; Herrington, L.; Folland, J. (Journal of Science and Medicine in Sport, 2024)
Objectives The aim of this study was to quantify changes in peak bending moments at the distal tibia, peak patellofemoral joint contact forces and peak Achilles tendon forces during a high-intensity run to fatigue at middle-distance speed.